Chemical Composition of Mish "A Traditional Fermented Dairy Product" from Different Plants During Storage - Mohamed Abdalla, Mohamed Osman; Abdel Nabi Ahmed, Somaia Zonnoon (Pakistan Journal of Nutrition, 2010)
This study was conducted to evaluate the chemical composition of mish during storage. Ninety samples of mish were collected on the day of manufacture (day one) from three different dairy plants (DP1, DP2, DP3), transported to the laboratory of the Department of Dairy Production, Faculty of Animal Production in ice box and stored at 7oC for 28 days. Samples were analyzed for fat, protein, total solids, ash and titratable acidity at 1, 7, 14, 21 and 28 days. The results showed that fat, protein, total solids, ash and titratable acidity were high in DP1 and low in DP2, except for fat content which was low in DP3. During storage fat, protein, total solids, ash contents and titratable acidity increased to a maximum at day 21 and then decreased thereafter, while titratable acidity steadily increased towards the end. Towards the end of storage, the fat content slightly decreased in DP1 and increased in DP2 and DP3. The protein content slightly decreased towards the end in DP1 and DP2 and increased in DP3. The total solids and ash contents slightly decreased in all three plants at the end of storage, while titratable acidity increased towards the end of storage in all plants.